Bidirectional Expression of Metabolic, Structural, and Immune Pathways in Early Myopia and Hyperopia - Riddell, Nina; Giummarra, Loretta; Hall, Nathan E.; Crewther, Sheila G. (Frontiers in Neuroscience, 2016)
Myopia (short-sightedness) affects 1.45 billion people worldwide, many of whom will develop sight-threatening secondary disorders. Myopic eyes are characterized by excessive size while hyperopic (long-sighted) eyes are typically small. The biological and genetic mechanisms underpinning the retina’s local control of these growth patterns remain unclear. In the present study, we used RNA sequencing to examine gene expression in the retina/RPE/choroid across 3 days of optically-induced myopia and hyperopia induction in chick. Data were analysed for differential expression of single genes, and Gene Set Enrichment Analysis (GSEA) was used to identify gene sets correlated with ocular axial length and refraction across lens groups. Like previous studies, we found few single genes that were differentially-expressed in a sign-of-defocus dependent manner (only BMP2 at 1 day). Using GSEA, however, we are the first to show that more subtle shifts in structural, metabolic, and immune pathway expression are correlated with the eye size and refractive changes induced by lens defocus. Our findings link gene expression with the morphological characteristics of refractive error, and suggest that physiological stress arising from metabolic and inflammatory pathway activation could increase the vulnerability of myopic eyes to secondary pathologies